Localized Intraoperative Virtual Endoscopy (LIVE) for Surgical Guidance in 16 Skull Base Patients. (January 2015) - Haerle, Stephan K.; Daly, Michael J.; Chan, Harley; Vescan, Allan; Witterick, Ian; Gentili, Fred; Zadeh, Gelareh; Kucharczyk, Walter; Irish, Jonathan C.
Importance: Previous preclinical studies of localized intraoperative virtual endoscopy–image-guided surgery (LIVE-IGS) for skull base surgery suggest a potential clinical benefit. Objective: The first aim was to evaluate the registration accuracy of virtual endoscopy based on high-resolution magnetic resonance imaging under clinical conditions. The second aim was to implement and assess real-time proximity alerts for critical structures during skull base drilling. Design and Setting: Patients consecutively referred for sinus and skull base surgery were enrolled in this prospective case series. Participants: Five patients were used to check registration accuracy and feasibility with the subsequent 11 patients being treated under LIVE-IGS conditions with presentation to the operating surgeon (phase 2). Intervention: Sixteen skull base patients were endoscopically operated on by using image-based navigation while LIVE-IGS was tested in a clinical setting. Main Outcome and Measures: Workload was quantitatively assessed using the validated National Aeronautics and Space Administration Task Load Index (NASA-TLX) questionnaire. Results: Real-time localization of the surgical drill was accurate to ~1 to 2 mm in all cases. The use of 3-mm proximity alert zones around the carotid arteries and optic nerve found regular clinical use, as the median minimum distance between the tracked drill and these structures was 1 mm (0.2-3.1 mm) and 0.6 mm (0.2-2.5 mm), respectively. No statistical differences were found in the NASA-TLX indicators for this experienced surgical cohort. Conclusions and Relevance: Real-time proximity alerts with virtual endoscopic guidance was sufficiently accurate under clinical conditions. Further clinical evaluation is required to evaluate the potential surgical benefits, particularly for less experienced surgeons or for teaching purposes.